Circulating tumor cells (CTC) and Cell-free DNA (cfDNA): Liquid biopsy for cancer diagnostics - Ono, Yasuha; Abe, Hiroyuki; Abe, Minako; Kono, Fumika; Saeki, Yukie; Nakamura, Ayaka (Personalized Medicine Universe, 2020)
Cancer has been the leading cause of death in Japan since 1981, and deaths due to cancer continue to rise. The early detection of cancer and determining therapeutic effect using noninvasive techniques are critical in the treatment of cancer. We conducted a study assaying both circulating tumor cells (CTCs) and cell-free DNA (cfDNA) using a small quantity of blood (5 mL) in order to explore the utility of using liquid biopsies to detect and monitor various types of cancers. Our results confirm that not only are CTCs detected in multiple types of cancers, but also that there is a clinical correlation between the number of CTCs and cancer progression and the presence or absence of tumor metastasis. Furthermore, a significant increase in cfDNA concentration levels between healthy volunteers and cancer patients was confirmed. The measurements of CTCs and cfDNA levels have clinical significance, and can be expected to play a larger role in the diagnosis and treatment of cancer in the near future.